PENDAMPINGAN PENGGUNAAN SISTEM INFORMASI KINERJA ATLET KONI KABUPATEN KENDAL - Zuliarso, Eri; Sulastri, Sulastri; Diartono, Dwi Agus; Februarianti, Herny (Intimas, 2024)
The community service activity titled "Assistance in the Use of Athlete Performance Information System for KONI Kendal Regency" aims to enhance the effectiveness of managing and monitoring athlete performance in Kendal Regency. The developed information system serves as a tool for documenting, managing, and analyzing athlete performance data in an integrated manner. Through this assistance, coaches, managers, and KONI administrators are expected to optimally utilize the information system, enabling more accurate and efficient monitoring of athlete development. The assistance process involved three lecturers and two students who provided intensive training on the use and benefits of the main features of the information system. The methods used included direct training, usage simulations, and Q&A sessions to ensure a deep understanding among the participants. Questionnaire results indicated that the majority of participants understood the main features and found the information system very helpful in monitoring athlete performance. With this information system, it is expected that the management of athlete performance data can be conducted in a more structured and systematic manner. Additionally, the technical support provided during the assistance has helped to overcome the operational challenges faced by the users. This activity not only directly benefits the coaches and administrators of KONI Kendal Regency but also contributes to the development of human resources in the field of sports management.